Verandah of violence the background to the Aceh problem - Reid, Anthony 1939- (Singapore University Press In association with University of Washington Press, 2006)
Probes the underlying causes of the conflict that has pitted Aceh against Jakarta, explaining why the Acehnese entered the Indonesian republic in 1945 with a determination to resist outside domination, and how these attitudes have shaped Aceh's relations with the Indonesian state.